Malaysia: factors influencing unemployment among graduates / Jamilah Laidin, Nor Azira Ismail and Shahiszan Ismail - Laidin, Jamilah; Ismail, Nor Azira; Ismail, Shahiszan (Universiti Teknologi MARA, Kedah, 2022)
The COVID-19 outbreak has reduced global economic growth, boosted unemployment, and exacerbated poverty and hunger (United Nation, 2021). According to the International Labour Organisation (ILO), there will be 207 million unemployed people worldwide in 2022, which will be a 21 million increase over what it was in 2019. The ILO also estimates that the total number of hours worked globally in 2022 will be roughly 2 percent below its pre-pandemic level when adjusted for population growth, which corresponds to a deficit of 52 million full-time equivalent occupations (assuming a 48-hour workweek). This pandemic will surely have an impact on the substantial population of young people who are jobless. The youth unemployment rate in 2021 was 17.89 percent, up 0.68 percent from the previous year. The majority of young people who are unemployed are graduate students. In Malaysia, the unemployment rate for new graduates for 2020 rose to 25 percent, up from 13.8 percent in 2019 (Consultant, 2021).